L’alternative quantitatif/qualitatif à l’épreuve des univers discursifs numériques - Marie-Anne Paveau (Corela)
There is not much historical and epistemological works on the issue of qualitative and quantitative approaches in the field of text and discourse analysis. In this paper, I propose to consider the symmetry between qualitativism and quantitativism, the nature of the linguistic knowledge produced, the way the context is taken into account and the relevance of either approach regarding web native discourse corpora.